Immunogenicity and safety of BPZE1, an intranasal live attenuated pertussis vaccine, versus tetanus–diphtheria–acellular pertussis vaccine: a randomised, double-blind, phase 2b trial. Issue 10379 (11th March 2023) - Keech, Cheryl; Miller, Vicki E; Rizzardi, Barbara; Hoyle, Christopher; Pryor, Melinda J; Ferrand, Jonathan; Solovay, Ken; Thalen, Marcel; Noviello, Stephanie; Goldstein, Peter; Gorringe, Andrew; Cavell, Breeze; et al.
Summary: Background: Bordetella pertussis epidemics persist as transmission remains unabated despite high acellular pertussis vaccination rates. BPZE1, a live attenuated intranasal pertussis vaccine, was designed to prevent B pertussis infection and disease. We aimed to assess the immunogenicity and safety of BPZE1 compared with the tetanus–diphtheria–acellular pertussis vaccine (Tdap). Methods: In this double-blind, phase 2b trial at three research centres in the USA, healthy adults aged 18–50 years were randomly assigned (2:2:1:1) via a permuted block randomisation schedule to receive BPZE1 vaccination followed by BPZE1 attenuated challenge, BPZE1 vaccination followed by placebo challenge, Tdap followed by BPZE1 attenuated challenge, or Tdap followed by placebo challenge. On day 1, lyophilised BPZE1 was reconstituted with sterile water and given intranasally (0·4 mL delivered to each nostril), whereas Tdap was given intramuscularly. To maintain masking, participants in the BPZE1 groups received an intramuscular saline injection, and those in the Tdap groups received intranasal lyophilised placebo buffer. The attenuated challenge took place on day 85. The primary immunogenicity endpoint was the proportion of participants achieving nasal secretory IgA seroconversion against at least one B pertussis antigen on day 29 or day 113. Reactogenicity was assessed up to 7 days after vaccination and challenge, and adverse events were recorded for 28 days after vaccination and challenge. Serious adverse events were monitored throughout the study. This trial is registered with ClinicalTrials.gov, NCT03942406 . Findings: Between June 17 and Oct 3, 2019, 458 participants were screened and 280 were randomly assigned to the main cohort: 92 to the BPZE1–BPZE1 group, 92 to the BPZE1–placebo group, 46 to the Tdap–BPZE1 group, and 50 to the Tdap–placebo group. Seroconversion of at least one B pertussis- specific nasal secretory IgA was recorded in 79 (94% [95% CI 87–98]) of 84 participants in the BPZE1–BPZE1 group, 89 (95% [88–98]) of 94 in the BPZE1–placebo group, 38 (90% [77–97]) of 42 in the Tdap–BPZE1 group, and 42 (93% [82–99]) of 45 in the Tdap–placebo group. BPZE1 induced broad and consistent B pertussis -specific mucosal secretory IgA responses, whereas Tdap did not induce consistent mucosal secretory IgA responses. Both vaccines were well tolerated, with mild reactogenicity and no serious adverse events related to study vaccination. Interpretation: BPZE1 induced nasal mucosal immunity and produced functional serum responses. BPZE1 has the potential to avert B pertussis infections, which ultimately could lead to reduced transmission and diminished epidemic cycles. These results should be confirmed in large phase 3 trials. Funding: ILiAD Biotechnologies.